Interactive climate-soil forces shape the spatial distribution of foliar N:P stoichiometry in Vaccinium uliginosum planted in agroforests of Northeast China - Duan, Yadong; Guo, Baitao; Zhang, Lei; Li, Jinxia; Li, Sen; Zhao, Wenbo; Yang, Guang; Zhou, Shuang; Zhou, Chunwei; Song, Penghui; Li, Pengju; Fang, Lei; et al. (Frontiers in Ecology and Evolution, 2022)
Shrubs that can ripen to fruit are preferred to be used as an alternative source of ecological products instead of timber harvest in regions with a forest logging ban. The introduction of cultured shrubs from their habitat to newly developed lands has to be decided according to stand nutrient availability. Foliar nitrogen (N) and phosphorus (P) stoichiometry is an easily measured and reliable parameter to fast indicate possible limits in imbalanced N-P availabilities. Mapping the spatial distribution of foliar N:P ratio of in an objective shrub species can benefit exploring its potential acclimation to the N-P imbalance caused by joint forces of soil property and regional climate. In this study, Vaccinium uliginosum was taken as an objective shrub species and its cultivated populations were investigated in agroforests of Northeast China. A total of 51 populations were selected from 51 managed stands where 34 were in forests and 17 on farmlands. Foliar N and P concentration, soil physical and chemical properties, and topography were investigated in 2018 and regional climatic factors were assessed by averaged previous-5-year records (2013-2018). V. uliginosum was determined to have a foliar N:P ratio lower than 4.4, which can be characterized as a limit of N relative to that of P. On forested lands, soil pH negatively impacted regressed foliar N:P, which was also part of contributions of soil total P content and average temperature to foliar N concentration. On farmlands, soil pH also resulted in a reduced foliar N:P ratio with joint contributions of ammonium N, nitrate N, and available P contents in soils and air humidity. Spatial interpolation indicated that western forests can benefit introduced V. uliginosum with a higher foliar N concentration, while introduction to eastern farmlands can lead to a higher foliar N:P ratio up to 14.6. Our study demonstrates recommended locations with expected soil and meteorological conditions by mapping spatial distributions, which can be referred to by other species and regions.